Perancangan Sistem Rencana Anggaran Biaya (Studi Kasus pada Merapi Jaya Sablon Bandung) - Mochamad Rezky Satria Koswara; Leni Nur Pratiwi (Ma'soem University, 2020)
Nowadays, the technology still continues to develop, various technologies are made to facilitate the people to conduct activities. technologies needed today is information. Information is primary needs which is very important for the company. Technology can make an accurate calculation tool to help a job. With a combination of information system and the function of a budget can increase the opportunity for companies to achieve company’s goal. Merapi Jaya Sablon is a SME’s who engaged in screen printing services. The management of the company does not have a budget plan and it cause cash outlays inefficiently.